PERSEPSI SISWA DALAM PENGGUNAAN APLIKASI WHATSAPP PADA PEMBELAJARAN AKIDAH AKHLAK KELAS V DI MI QUBA KOTA SORONG SELAMA MASA PANDEMI COVID-19 - Lidya Widiyanti Manege; Muhammad Ramli (MISOOL: Jurnal Pendidikan Dasar, 2020)
Does the research aim to find out: 1) How are students' perceptions? using the WhatsApp Application in learning during the pandemic; 2) what only the obstacles experienced by students in using the WhatsApp application learning Akidah Akhlak safe during the pandemic. This research uses a Descriptive Qualitative approach in which this research looks at the phenomena that occur around. By using data through interviews and documentation. After The data collected means that the research instrument used is valid. Based on interviews with teachers and also students that the perception of students in the use of the WhatsApp application in learning Akidah Akhlak during the pandemic period has a positive effect and can be accepted by teachers and students.